2005
DOI: 10.1002/anie.200501002
|View full text |Cite
|
Sign up to set email alerts
|

Protonated Isobutene in Zeolites: tert‐Butyl Cation or Alkoxide?

Abstract: Acid zeolite catalysts are industrially used for a variety of hydrocarbon transformation processes. Initially it was assumed that these reactions follow mechanisms known from chemistry in superacidic media, and involve carbocations as intermediates formed upon protonation of hydrocarbons by Brønsted acid sites.[1] However, NMR spectroscopic studies failed to find simple carbenium ions as intermediates, and instead produced evidence for surface alkoxides. [2,3] Around the same time, quantum chemical calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
117
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 36 publications
4
117
1
Order By: Relevance
“…Inclusion of zero-point vibrations and finite temperature effects further stabilized the carbenium ions relative to the covalently bound alkoxides. It was concluded that already at 120 K formation of tert-butyl cation in H-ferrierite becomes thermodynamically more favorable than formation of the covalently bound species [37]. However, this theoretical prediction lacks the experimental support, because simple carbenium ions have never been observed by either NMR or infrared spectroscopy upon olefin adsorption to hydrogen forms of zeolites [38].…”
Section: Activation Of Hydrocarbons In Zeolites: the Role Of Dispersimentioning
confidence: 94%
See 3 more Smart Citations
“…Inclusion of zero-point vibrations and finite temperature effects further stabilized the carbenium ions relative to the covalently bound alkoxides. It was concluded that already at 120 K formation of tert-butyl cation in H-ferrierite becomes thermodynamically more favorable than formation of the covalently bound species [37]. However, this theoretical prediction lacks the experimental support, because simple carbenium ions have never been observed by either NMR or infrared spectroscopy upon olefin adsorption to hydrogen forms of zeolites [38].…”
Section: Activation Of Hydrocarbons In Zeolites: the Role Of Dispersimentioning
confidence: 94%
“…Only the π-complex of butane (1) with the Brønsted acid site of the zeolite was found to be more stable than the isolated alkene separated from the zeolite [37]. The stabilization however was rather minor (PBE/PW, FER pbc , Table 11.1).…”
Section: Activation Of Hydrocarbons In Zeolites: the Role Of Dispersimentioning
confidence: 96%
See 2 more Smart Citations
“…Because of technical limitations vibrational analysis, which could prove that this cation is a local minimum on the potential energy surface, that is a metastable species, have only recently been made. Within a periodic DFT study of isobutene/H-FER a complete vibrational analysis for all atoms in the unit cell was made [48], and as part of a hybrid QM/MNDO study on an embedded cluster model of isobutene/H-MOR a vibrational analysis was made with a limited number of atoms [49]. Both reached the + H + -H 2 -H + (6) (7) Figure 22.9 Carbenium ion, 6, obtained by hydride abstraction from xylene and its deprotonation product, 7.…”
Section: Stability Of Carbenium Ions In Zeolitesmentioning
confidence: 99%